Tailoring Ferrimagnetic Transition Temperatures, Coercivity Fields, and Saturation Magnetization by Modulating Mn Concentration in (CoCrFeNi)1−xMnx High-Entropy Alloys - Lee, Chi-Hung; Chin, Hsu-Hsuan; Zeng, Kun-Yuan; Chang, Yao-Jen; Yeh, An-Chou; Yeh, Jien-Wei; Lin, Su-Jien; Wang, Chun-Chieh; Glatzel, Uwe; Huang, E-Wen (Frontiers in Materials, 2022)
Cr and Mn play intriguing roles in determining the magnetic properties of CoFeNi-based high-entropy alloys (HEA). In this study, we tune the stoichiometric Mn composition to systematically explore the magnetic properties of (CoCrFeNi)1−xMnx HEAs. We observe a change from ferro- to ferrimagnetism due to the incorporation of Mn atoms into the CoCrFeNi HEA. In addition, we measure an 81% reduction in magnetization with the incorporation of 7.6(2)% Mn atoms. Such a significant reduction in magnetization cannot be solely explained by the effect of the inversed moments on the Mn atoms. Hence, we propose a mechanism whereby the Mn atoms flip the moments of neighboring atoms, which results in the magnetization reduction observed in the CoFeNi-based HEAs.